Bandgap reference, temperature sensor and low drop-out regulator circuits monolithic sensors in TPSCo 65 nm ISC technology. (1st February 2023) - Yelkenci, A.; Qui, S.; Rossewij, M.J.; Grelli, A.; Gajanana, D.; Gromov, V.
Abstract: With Inner Tracking System v3 (ITS3), the ALICE experiment is pursuing a wafer-scale Monolithic Active Pixel Sensor (MAPS). The chip is being developed in TPSCo 65 nm ISC technology which is under study in the framework of CERN EP R&D on monolithic sensors for High Energy Physics (HEP) applications. This contribution presents designs and measurement results of building blocks needed for this chip, in particular bandgap references and temperature sensors. In addition, simulation results of the design of Low Drop-out Regulator (LDO) to be submitted for the next prototyping run will be discussed.